Teaching Model Development of English Vocabulary Mastery by Using Natural Adventure and Learning (NAL) - Putri Novita Nainggolan; Arsen Nahum Pasaribu; Erika Sinambela (Merwin Publisher, 2024)
The research aims is to describe the problem of writing ability in junior high school needs to be done to observe the development of students'' learning difficulties incurrent writing skills. The type of research is a class action research descriptive quantitative. population of this research is class VIII at Junior High School state Hutabayuraja. Based on the results of the pre-test, the pre-test mean score was 39,66 and the mean score in the post-test was 86,43. It can be seen that the students'' skill in speaking by using storytelling technique increased. From these calculations, it can be inferred that there was a difference of students'' scores before and after receiving the treatment. The affect storytelling used single story telling is from score minimum pre-test 30 to score post test is 82 and score maximal pre-test 65 and post-test is 82 it is mean the research is succeed and have affect to writing skill. The improving from the research is when using the single story telling model, the results obtained increased by approx. 49%. Consequently, these data which had been analyzed answered the first research question that using storytelling can improve student writing ability at Junior High School state three Hutabayuraja at class eight. Based on the data analysis, the researcher found that storytelling technique can improve students’ skill in speaking. As the result from the pre-test and post-test mean scores which were given. The improvement of mean score was 39,66 to 86,43.It means that there is significant difference of achievement between the students who were taught by using storytelling technique and the students who were taught with out story telling technique.The data also showed that students felt that vocabulary mastery technique could help them in writing.